Pengaruh Literasi Digital terhadap Intensi Berwirausaha dengan Kreativitas Kewirausahaan sebagai Variabel Intervening pada Mahasiswa di Universitas Negeri Jakarta - Tajul Fuzari (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of digital literacy on entrepreneurial intention with entrepreneurial creativity as an intervening variable among students at Universitas Negeri Jakarta. This research employed a quantitative approach using a survey method. The research sample consisted of 397 active students from eight faculties at Universitas Negeri Jakarta, selected using the Proportionate Stratified Random Sampling technique. The data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results indicate that digital literacy has a positive and significant effect on entrepreneurial intention. Digital literacy also has a positive and significant effect on entrepreneurial creativity. In addition, entrepreneurial creativity is proven to have a positive and significant effect on entrepreneurial intention. The indirect effect test shows that entrepreneurial creativity is able to partially mediate the effect of digital literacy on students entrepreneurial intention. These findings indicate that increasing students entrepreneurial intention can be achieved not only by strengthening digital literacy skills, but also by developing entrepreneurial creativity so that students are able to transform their digital abilities into innovative and valuable business ideas. This study implies that higher education institutions need to design digital entrepreneurship programs that focus not only on technological mastery, but also on fostering creativity, innovation, and students readiness to establish businesses.